Coffee Entrepreneur Training for Karang Taruna Members, at Kedai Durian Urban Village, Medan City - Lubis, Mia Aulina; Putri, Malida (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Karang Taruna, Kedai Durian Urban village, is one of the youth groups in Medan Johor Sub-District, Medan City. They actively organize social and economic activities for members and the surrounding community. In economic activity, Karang Taruna Kedai Durian already sells coffee beans. This business is run by Karang Taruna, Kedai Durian members but has not run well due to a lack of understanding and skills in running a business. This Coffee Entrepreneur training seeks to provide solutions to have competence or expertise in running a coffee business to develop and have competitiveness in the market. Activities carried out to achieve the goal of devotion are coffee brewing training, marketing training, socialization on the importance of entrepreneurship. The training results showed a significant increase in skills and increased spirit and interest of young people to grow their existing businesses. This Coffee Entrepreneur Service Training to the Community has completed most activities with good acceptance from Karang Taruna, Kedai Durian Urban Village.